Indoor dispersion of airborne nano and fine particles: Main factors affecting spatial and temporal distribution in the frame of exposure modeling. (3rd July 2019) - Belut, Emmanuel; Sánchez Jiménez, Araceli; Meyer‐Plath, Asmus; Koivisto, Antti Joonas; Koponen, Ismo K.; Jensen, Alexander C. Ø.; MacCalman, Laura; Tuinman, Ilse; Fransman, Wouter; Domat, Maidá; Bivolarova, Mariya; van Tongeren, Martie
Abstract: A particle exposure experiment inside a large climate‐controlled chamber was conducted. Data on spatial and temporal distribution of nanoscale and fine aerosols in the range of mobility diameters 8‐600 nm were collected with high resolution, for sodium chloride, fluorescein sodium, and silica particles. Exposure scenarios studied included constant and intermittent source emissions, different aggregation conditions, high (10 h −1 ) and low (3.5 h −1 ) air exchange rates (AERs) corresponding to chamber Reynolds number, respectively, equal to 1 × 10 5 and 3 × 10 4 . Results are presented and analyzed to highlight the main determinants of exposure and to determine whether the assumptions underlying two‐box models hold under various scenarios. The main determinants of exposure found were the source generation rate and the ventilation rate. The effect of particles nature was indiscernible, and the decrease of airborne total number concentrations attributable to surface deposition was estimated lower than 2% when the source was active. A near‐field/far‐field structure of aerosol concentration was always observed for the AER = 10 h −1 but for AER = 3.5 h −1, a single‐field structure was found. The particle size distribution was always homogeneous in space but a general shift of particle diameter (−8% to +16%) was observed between scenarios in correlation with the AER and with the source position, presumably largely attributable to aggregation.